Competitive Advantage Analysis of Soybean Farming in Indonesia - Bernadeta Julia Wijaya Puspita Sari; Sucihatiningsih Dian Wisika Prajanti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2016)
Soybean is one of the commodities strategy, because the demand for soy in the international and domestic market has always increased. To fill the domestic soybean demand by importing soybeans. This is a serious problem because it will have an impact on the decline in farm income due to import soybeans. The aim of this study was to determine whether soybean farming in the village Banaran, Pracimantoro, Wonogirihas a competitive advantage and comparative advantage, as well as to determine the impact of government policy on soybean farming.The method used is qualitative method by interviews with soybean farmers. Results of interview with farmers processed by Policy Analysis Matrix (PAM), which produced the analysis forms of competitive advantage, comparative advantage, and the impact of government policy.Results from this study are of soybean farming in the village Banaran, Pracimantoro, Wonogiri only has a competitive advantage.Overall government policies protective of soybean farming in the village Banaran.